Transport mechanisms of water molecules and ions in sub-nano channels of nanostructured water treatment liquid-crystalline membranes: a molecular dynamics simulation study. Issue 3 (12th December 2019) - Nada, Hiroki; Sakamoto, Takeshi; Henmi, Masahiro; Ogawa, Takafumi; Kimura, Masahiro; Kato, Takashi
Abstract : Transport mechanisms of water molecules and ions in the liquid crystalline (LC) membranes with sub-nano channels formed by self-organization of thermotropic ionic LC compounds were elucidated by molecular dynamics simulations. Abstract : Membranes with sub-nano channels formed by self-organization of ionic liquid-crystalline (LC) compounds have great potential as water treatment membranes. In this study, the transport mechanisms of water molecules and ions in the sub-nano channels of the LC membranes are investigated by molecular dynamics simulations for NaCl and NaNO3 solutions. The simulation results suggest that there are different transport mechanisms for water molecules and ions; the transport of water molecules occurs by Brownian diffusion, whereas that of ions occurs by jump diffusion between particular sites in the sub-nano channel. A free-energy landscape of an ion in the channel is analyzed using a metadynamics method, which indicates distinct local minima at particular sites and supports the jump diffusion mechanism. The effects of the LC compounds' structural flexibility and the electrostatic interaction with the wall of the sub-nano channels on the permeability of water molecules and ions are also investigated by molecular dynamics simulations. Simulation results suggest both the structural flexibility and the electrostatic interaction, which are characteristics of the LC membranes, are important factors in determining the water treatment performance. The structural flexibility affects the permeability of the membrane to water molecules and the electrostatic interaction reduces the permeability to ions.